Intergenerational Brand Transfer on Cosmetics Products - Ting, Su-Ding (Asian Business Review, 2020)
The study examined intergenerational brand transfer from mother to daughter for cosmetics products using evolutionary psychology as the framework. Data were collected from 30 participants (14 mothers, 16 daughters) using in-depth semi-structured interviews. The results showed a strong intergenerational transfer of brand loyalty. Most of the daughters used either the full range (25%) or a part of the range (50%) of cosmetics products used by their mothers. A majority (87.5%) of the daughters reported that they knew the cosmetics brands used by their mothers, and the interviews with their mothers showed that 75% of them accurately remembered the brands. The mothers’ influence was achieved through brand visibility, daughters’ trial use of the cosmetics, and the mothers acting as product suppliers. Price and product characteristics ranked the highest among the daughters’ and mothers’ considerations in purchasing cosmetics, showing that the daughters had adopted their mothers’ behavior and thinking in product selection. The extended family also influenced the daughters’ choice of cosmetics brands because of the close-knit community.
Keywords: intergenerational brand transfer; brand loyalty; brand visibility; brand knowledge